2002
DOI: 10.1364/ao.41.000239
|View full text |Cite
|
Sign up to set email alerts
|

X-ray multilayer monochromator with enhanced performance

Abstract: An x-ray multilayer monochromator with improved resolution and a low specular background is presented. The monochromator consists of a lamellar multilayer amplitude grating with appropriate parameters used at the zeroth diffraction order. The device is fabricated by means of combining deposition of thin films on a nanometer scale, UV lithography, and reactive ion etching. The performance of this new monochromator at photon energies near 1500 eV is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although the 0th order bandwidth was reduced by a factor of two to five, 143-145 the achieved efficiency was also reduced 149 by 38% to even 85% relative to a standard ML mirror. 143,144 Kozhevnikov et al then identified the single-order operating regime for the multilayer grating. 146,147 In this scheme, only one diffraction order will be excited and the reflected power is concentrated in this single order, if the angular width of the zeroth or higher order peak is much smaller than the angular distance between the adjacent orders.…”
Section: Single Order Lamellar Multilayer Gratingmentioning
confidence: 99%
“…Although the 0th order bandwidth was reduced by a factor of two to five, 143-145 the achieved efficiency was also reduced 149 by 38% to even 85% relative to a standard ML mirror. 143,144 Kozhevnikov et al then identified the single-order operating regime for the multilayer grating. 146,147 In this scheme, only one diffraction order will be excited and the reflected power is concentrated in this single order, if the angular width of the zeroth or higher order peak is much smaller than the angular distance between the adjacent orders.…”
Section: Single Order Lamellar Multilayer Gratingmentioning
confidence: 99%
“…Multilayer gratings or etched multilayers (EMs), consisting in a periodic stack of bilayers with nanometric thickness laterally etched according to a periodic pattern, belong to this class of two‐dimensional photonic crystals that has opened up new ways for X‐ray optics. Thus, lamellar (or laminar) multilayer gratings can be used as efficient polychromators and are also implemented as improved monochromators with respect to mere multilayer Bragg mirrors for the soft X‐ray domain . Recently, we have demonstrated that EMs can be used as dispersive element of curved crystal‐soft X‐ray spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…The multilayer gratings (MGs), consisting of a periodic stack of bilayers with nanometric thickness laterally etched according to a periodic pattern, belong to this class of 2D photonic crystals that has opened up new ways for x-ray optics. Thus lamellar multilayer gratings (LMGs) can be used as efficient polychromators [1] and can also be implemented as improved monochromators with respect to mere multilayer Bragg mirrors for the soft-x-ray domain [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%